2017
DOI: 10.3389/fnins.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

ASPP2 Plays a Dual Role in gp120-Induced Autophagy and Apoptosis of Neuroblastoma Cells

Abstract: HIV invasion of the central nervous system (CNS) in the majority of patients infected with HIV-1, leads to dysfunction and injury within the CNS, showing a variety of neurological symptoms which was broadly termed HIV-associated neurocognitive disorder (HAND). But the molecular mechanisms are not completely understood. It has been suggested that apoptosis and autophagic dysfunction in neurons may play an important role in the development of HAND. Previous studies have indicated that p53 may be involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…One study indicated that ASPP2 could promote Ras-induced senescence through the direct interaction of its N-terminus with Ras-GTP (9). Furthermore, it serves as a pivotal regulator of cell polarity and the autophagy process (10,11). ASPP2 has also been confirmed to bind and co-localize with PAR3, thereby inhibiting tumor metastasis as a molecular switch of epithelial-mesenchymal transition (EMT), and the reduction of ASPP2 results in the poor survival and prognosis of patients with hepatocellular carcinoma and breast cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…One study indicated that ASPP2 could promote Ras-induced senescence through the direct interaction of its N-terminus with Ras-GTP (9). Furthermore, it serves as a pivotal regulator of cell polarity and the autophagy process (10,11). ASPP2 has also been confirmed to bind and co-localize with PAR3, thereby inhibiting tumor metastasis as a molecular switch of epithelial-mesenchymal transition (EMT), and the reduction of ASPP2 results in the poor survival and prognosis of patients with hepatocellular carcinoma and breast cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…As a member of ASPP family, the function of ASPP2 is potentially controlled by its binding partners and localisation. When ASPP2 locates at the cytosol/nucleus, ASPP2 enhances p53‐induced apoptosis in cancer cells [15,18,19], whereas in the cell junctions, it binds and maintains the integrity of cell polarity and adherence junction via its N‐terminus [20,21]. In this study, ASPP2 protein was stained with green fluorescence, which was expressed in the perinuclear cytoplasm and/or the nucleus in ESCC cells by immunofluorescence.…”
Section: Discussionmentioning
confidence: 78%
“…It is a common knowledge that HIV induces T‐cell apoptosis . Several studies have shown that HIV‐1 and its molecules (gp120, Nef) can also mediate neuroblastoma, breast, colorectal, prostate cancer cell growth inhibition and apoptosis. An interesting possibility, explaining lower frequency of several cancers in HIV‐infected persons, is that the HAART drugs can possess cancer‐prevention or antineoplastic activity.…”
Section: Hiv and Cancer Risks In The Haart Eramentioning
confidence: 99%